MENANAMKAN PENDIDIKAN KARAKTER MELALUI SEJARAH HIDUP MARIA WALANDA MARAMIS DALAM MEMPERJUANGAKAN HAK PEREMPUAN DI INDONESA - Suci Adelsa; Anny Wahyuni; Budi Purnomo (Al-Fikru : Jurnal Pendidikan Dan Sains, 2021)
The women's movement in Indonesia is one of the most highlighted things where the women's movement in Indonesia is proof that women in Indonesia have an active contribution and role in fighting for independence, fighting for education and elevating the degree and rights of women in Indonesia which, Previously, women in Indonesia were not considered too much and more considered as weak people so that the existence of this women's movement made the status of women more considered better and their existence more respected. As Maria Walanda Maramis struggles for education and women's rights in Indonesia, so that women in Indonesia are especially women who live in Minahasa District, North Sulawesi Province and have an influence on women throughout Indonesia. Keywords ; Maria Walanda Maramis "Fighting For Women's Rights"